Rationales and Instruments for Public Innovation Policies - Takalo, Tuomas (Journal of Reviews on Global Economics, 2012)
Abstract: Economic interest in innovation policy largely arises from the fundamental importance of innovation to social welfare and from inefficiencies in innovation in a competitive market environment. As a result, a wide variety of public innovation policies are used in practice. This study reviews the economic justifications for public innovation policies and compares the existing policy tools, paying particular attention to the Finnish innovation policy environment.